QSAR modelling to predict structural features of certain sulfonamide as Urokinase-type Plasminogen Activator inhibitors - Jawarkar, Rahul D; Zaki, Magdi E A; Al-Hussain, Sami; Alzahrani, Abdullah Yahya Abdullah; Long, Chiau Ming *; Samad, Abdul; Ingle, Rahul G.; Mali, Suraj N. (Elsevier, 2024)
The serine hydrolase family includes serine proteases. It is essential for hydrolyzing protein peptide bonds and breaking them. The urokinase-type plasminogen activator (uPA) selectively binds to the uPAR on numerous cell types, including cancer cells. Pericellular proteolysis of cell-bound proteins requires this interaction. High uPA and uPAR levels regularly worsen cancer prognoses. Thus, small chemical active-site inhibitors that block uPA may diminish cancer cell invasion and metastasis. In compliance with Organization for Economic Corporation and Development guidelines, this research performed a complete Quantitative structure activity relationship analysis of sulfonamide compounds as Urokinase-type Plasminogen Activator inhibitors. Py-Descriptors were used for this investigation. PyDescriptor uses PyMOL standards and idioms to calculate 11,145 simple molecular descriptors. This plugin calculates molecular descriptors irrespective of molecular representation properties like atom numbering or labelling, spatial reference frame, translational and rotational invariance, etc. The investigation sought to find essential and hidden structural characteristics that regulate sulfonamide-type drugs’ Urokinase-type Plasminogen Activator Inhibitory action. Twenty-eight sulfonamide chemicals are used in the Quantitative structure activity relationship study to generate statistically robust and highly predictive univariate and multivariate models. All models were thoroughly evaluated and meet several statistical parameter thresholds (e.g., R 2 =0.9259–0.9280, Q 2 Loo =0.8579–0.8558, Q 2 LMO =0.8013–0.7865). The analysis reveal that occurance of ring carbon atoms exactly at 3 A0 from carbon atom, number of negatively charged atoms from sulphur atoms within 5 bonds, presence of hydrogen atom exactly at 3 bonds from donar atoms, presence of carbon atom exactly at 4 A0 from donar atom, presence of acceptor atom exactly at 5 A0 from sulphur atom and sum of partial charges of lipo atoms within 6 bonds from sulphur atom are important pharmacophoric features for Urokinase- type Plasminogen Activator Inhibition binding affinity. Thus, the developed Quantitative structure activity relationship study has an equilibrium of quantitative and qualitative tactics. The results could be useful for future optimizations of sulfonamide analogues.